2015
DOI: 10.1016/j.piutam.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Transition in a Flared Cone Boundary Layer at Mach 6

Abstract: Laminar-turbulent transition is investigated for a flared cone at Mach 6 using spatial Direct Numerical Simulations (DNS). The flow parameters used in the simulations discussed here closely match the laboratory conditions of the hypersonic transition experiments conducted at Purdue University. The objective of the present research is to make a contribution towards understanding of the nonlinear stages of transition in hypersonic boundary layers on a flared cone. Towards this end, the role of second-mode fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The dominant mechanism appearing in these conditions relies on the amplification of broadband first oblique modes in the boundary layer, beating the second mode growth because of their upstream domain of instability. These oblique modes interact nonlinearly to create streaks such as already documented in many cases of supersonic and hypersonic transition (Fasel et al 1993;Laible et al 2009;Mayer et al 2011;Franko & Lele 2013Fasel et al 2015). Then, the nonlinear forcing linked to those streaks trigger a linear amplification mechanism, either due to centrifugal, baroclinic or the lift-up effect, in the mixing layer and reattachment region which lead to breakdown.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The dominant mechanism appearing in these conditions relies on the amplification of broadband first oblique modes in the boundary layer, beating the second mode growth because of their upstream domain of instability. These oblique modes interact nonlinearly to create streaks such as already documented in many cases of supersonic and hypersonic transition (Fasel et al 1993;Laible et al 2009;Mayer et al 2011;Franko & Lele 2013Fasel et al 2015). Then, the nonlinear forcing linked to those streaks trigger a linear amplification mechanism, either due to centrifugal, baroclinic or the lift-up effect, in the mixing layer and reattachment region which lead to breakdown.…”
Section: Resultsmentioning
confidence: 84%
“…2011; Franko & Lele 2013, 2014; Fasel et al. 2015). Then, the nonlinear forcing linked to those streaks trigger a linear amplification mechanism, either due to centrifugal, baroclinic or the lift-up effect, in the mixing layer and reattachment region which lead to breakdown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the fundamental breakdown simulated by Laible and Fasel [236] and Laible [241] was controlled rather than being caused by a natural scenario, they observed streamwise vortices (referred to as 'streaks') on the cone surface that were similar to those observed in quiet-tunnel experiments [9,180]. Fasel and coworkers [238,243] also performed DNS to investigate the fundamental breakdown on another ŕared cone at Mach 6, with the cone geometry and ŕow conditions representative of the experiments in the BAM6QT at Purdue University. Similar to the DNS of the ŕow over the NASA ŕared cone [236,241], the breakdown to turbulence over the Purdue ŕared cone was simulated using a disturbance input with speciőed frequency and azimuthal wavenumber.…”
Section: B Flows Over Flared Conesmentioning
confidence: 83%
“…The DNS conőrmed the typical pattern of 'hot' and 'cold' streaks appearing, disappearing and then reappearing in the strongly nonlinear transition regime close to the őnal breakdown. Fasel et al [243] further showed that the oblique breakdown can be another viable path to turbulence. They reported that this type of breakdown was only initiated by one pair of oblique second-Mack-mode disturbance waves with the same frequency and azimuthal wavenumbers, but with opposite sign.…”
Section: B Flows Over Flared Conesmentioning
confidence: 99%